Akuntansi Pertanggungjawaban Sosial dan Lingkungan : Konsep, Implementasi, dan Tantangan - Imelda Saputri; Ersi Sisdianto (Jurnal Riset Akuntansi, 2024)
Social and Environmental Responsibility Accounting (APSL) is increasingly important in the business world along with increasing attention to sustainability issues. This approach involves reporting that not only covers financial aspects, but also the social and environmental impacts caused by company activities. APSL's main goal is to increase transparency, accountability, and encourage responsible business practices towards society and the environment. APSL implementation involves identifying significant social and environmental issues, measuring impacts, and reporting that complies with international standards. Even though regulations related to social and environmental responsibility already exist, challenges in implementing APSL remain, including lack of understanding, high implementation costs, and regulatory inconsistencies between countries. The implementation of Good Corporate Governance (GCG) mechanisms that involve all stakeholders is expected to support the success of APSL and increase the credibility of social and environmental reporting. The company's success in implementing APSL shows that this strategy is not only beneficial for reputation, but also contributes to long-term economic sustainability.